Narrative Strategy of Provocation in Novels of Clemens Setz - E. M. Shastina (Научный диалог, 2025)
This study explores the works of contemporary Austrian author Clemens J. Setz (b. 1982). It provides a comprehensive overview of the most significant novels published by the author from 2007 to 2023. The relevance of this research is underscored by the necessity to conceptualize the phenomenon of “Austrian literature” in the early 21st century. It is revealed that, on one hand, Setz continues the traditions of Austrian literature from the second half of the 20th century, while on the other hand, he experiments with narrative organization, employing various narrative strategies. The concept of narrative provocation is introduced as a facet of narrative strategy. Special attention is given to Setz's distinctive authorial style and the unique organization of his narratives. It is demonstrated that narrative provocation shapes the author's intentions, “organizes” the communication between the narrator and the reader, and reveals the peculiarities of Setz's novelistic poetics. The novelty of this research lies in the fact that Setz's oeuvre has not yet been a subject of study in Russian literary scholarship. The methodological foundation of this work is based on studies by both foreign and domestic scholars concerning Austrian literature, as well as the nature of narrative strategy, which encompasses narrative worldview, narrative modality, and narrative intrigue (V. I. Tyupa).